2013
DOI: 10.1186/1465-9921-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of GSK-3 in a guinea pig model of LPS-induced pulmonary inflammation: II. Effects on skeletal muscle atrophy

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is accompanied by pulmonary inflammation and associated with extra-pulmonary manifestations, including skeletal muscle atrophy. Glycogen synthase kinase-3 (GSK-3) has been implicated in the regulation of muscle protein- and myonuclear turnover; two crucial processes that determine muscle mass. In the present study we investigated the effect of the selective GSK-3 inhibitor SB216763 on muscle mass in a guinea pig model of lipopolysaccharide (LPS)-induced pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Pharmacological inhibition of GSK3β attenuates TNF-α and glucocorticoid induced suppression of MyoD expression and myotube formation in C2C12 and primary satellite cells (Ma et al, 2014, Verhees et al, 2013). TDZD-8 also improved muscle strength and Pax7 expression (a marker for satellite cells) in HSA LR mice, a mouse model of myotonic dystrophy (Jones et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of GSK3β attenuates TNF-α and glucocorticoid induced suppression of MyoD expression and myotube formation in C2C12 and primary satellite cells (Ma et al, 2014, Verhees et al, 2013). TDZD-8 also improved muscle strength and Pax7 expression (a marker for satellite cells) in HSA LR mice, a mouse model of myotonic dystrophy (Jones et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, IGF-1/Akt controls two protein synthetic pathways via mTORC1 and GSK3β. Although these pathways are decreased in various muscle atrophy conditions [ 16 , 17 , 18 , 19 ], the exact relationship and interaction between these pathways in skeletal muscle atrophy and hypertrophy conditions remain to be determined. IGF-1 also affects protein synthesis via myostatin signaling, and the mechanism is discussed below.…”
Section: Muscle Protein Synthesis and Igf-1 Signalingmentioning
confidence: 99%
“…Moreover, it has been presented that activation of the GSK3β signal pathway leads to elevated expression of proteolysis markers, myogenesis disruption, and to muscle loss (Shen et al 2017 ). However, inhibition of GSK3β prevents muscle atrophy in mice (Shen et al 2017 ) and guinea pigs (Verhees et al 2013 ), and it further prevents development of myotonic dystrophy type 1 (DM1), eventually leading to skeletal muscle being characterized by higher fiber density, and normal fiber size (Wei et al 2018 ). Other researchers also observed that GSK3β is a negative regulator of skeletal muscle growth, and its insufficiency stimulates myogenic differentiation and myotube formation (van der Velden et al 2008 ; Ma et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%